Edukasi Dan Sosialisasi Perilaku Hidup Bersih dan Sehat (PHBS) Pada Masyarakat Desa Suka Raja - Siti Salwa Hanafiah; Syuaib Afri Mulana; Vioni Nabila Alyaza; Rosi Anggraini; Putri Kirana; Ayu Nani; Putri Lestari; Sri Handayani; Sulastri Asriatun; Sumarti Agustina; Suparmi Suparmi; Fitri Fitri; Indra Gunawan; Gita Sopianti; Desi Febriani; Muhammad Fajri; Rina S.E Sitindaon (JURNAL PENGABDIAN KADER BANGSA, 2025)
Education and socialization of clean and healthy living behavior (PHBS) is one of the important efforts to maintain environmental cleanliness and health. One behavior that needs serious attention is the habit of littering. The purpose of this counseling activity (PHBS) is to encourage the community to dispose of waste in its place which is carried out through direct communication in the Sukaraja Village community. The data processing method used in this activity is SPSS software, to make it easier to detect the data. Based on the results of data processing, it was found that 67.5% of respondents still burned waste because the community did not know how to properly manage waste while 12% of respondents said that they littered because there was no landfill, and 8.4% of respondents disposed of waste by piling it up because the community did not know how to properly manage waste and 4.8% of respondents threw waste in the river. Based on the data obtained, it can be concluded that the community still burns waste because the landfill has not been provided, but we can take this from this counseling and education activity to encourage the community to change healthy behavior such as disposing of waste in its place.